Varnost in zanesljivost v okoljski tehniki - Marn, Jure; Fras, Matjaž; Iljaž, Jurij (University of Maribor Press, 2021)
Safety and Reliability in Environmental Engineeering. This work represents first view into safety culture, in particular safety and reliability in the area of environmental engineering, and wider. Basic concepts such as safety, reliability, risk, failure, error and basic mechanism for their analysis such as fault tree and event tree are discussed.